The psychological impact of SARS-COV-2: assessing anxiety and wellbeing within university students in Bangladesh during the pandemic (Jahangirnagar University Journal of Biological Sciences, 2024)
The main focus of this study was to explore the emotional experiences of Jahangirnagar University students amid the COVID-19 pandemic, shedding light on their well-being and anxiety levels during this unprecedented time. Using a multidimensional approach, our descriptive and exploratory statistics reveal the demographic characteristics of the diverse group of students, including a skewed gender ratio attributed to the pandemic. Notably, living arrangements significantly influence emotional states, as students residing with their families report lower anxiety levels, indicating the potential protective role of familial support during crises. Online class attendance emerges as a pivotal factor impacting emotional well-being, with regular participation associated with higher levels of well-being, while sporadic or non-attendance correlates with heightened anxiety. The study further reveals the impact of part-time job loss during the pandemic on student emotional states, highlighting the economic strain experienced by many students. A substantial proportion of students’ report both moderate to severe anxiety and sufficient well-being, underscoring the complexity of emotional experiences during this tumultuous period. Binary logistic regression identifies gender-based disparities and social support as predictors of well-being and anxiety, while factor analysis illuminates the underlying structures of these constructs. In conclusion, these insights call for prioritizing mental health support and fostering conducive environments within academic institutions, particularly Jahangirnagar University, thereby facilitating student resilience and academic success during uncertain times.Jahangirnagar University J. Biol. Sci. 12(1 & 2): 55-71, 2023 (June & December)